Compression of the inferior vena cava due to hydatic liver cyst: Postoperative death - Piacenza, Guillermo; Mesa, Guillermo; Cassinelli, Daniel (Cirugía del Uruguay, 1974)
A patient with hydatid cyst on right lobe of liver suffered from compression of postcava. Post-operatory evolution of surgery performed on cyst ended with the patient's death ten hours later due to acute cardiovascular decompensation. The paper discuses pausible caus of death.